COMPUTER ALGORITHMS FOR EVALUATION OF SPARKING INDICATED BY OPTOELECTRONIC SPARKING ANALYZER - W. Zelinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Optoelectronic sparking analyzer provides the possibility to realize a number of algorithms that permit to convert indicated light signals containing information on number of sparkings in the measuring cycle and their intensity divided in ten classes. The paper presents the selected sparking indices converted with the help of a computer and these indices make it possible to evaluate sparking level of separate commutator sectors by calculating average values in the whole measuring cycle of brush-commutator contact in dc machines. The paper also contains limiting values of the presented indices.